Aplikasi Sistem Ujian Berbasis Web dan Mobile Pada SMK Perintis Kabupaten Bandung Provinsi Jawa Barat - Uddin, Badie; Azis, Idris Abdul; Dhika, Harry; Liani, Noval (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The Mid-Semester Examination (UTS) and Final Semester Examination (UAS) at PerintisVocational School are still carried out manually. To familiarize students and teachers in facing theComputer-Based National Examination (UNBK) held by the Department of Education and in order toparticipate in implementing the government's Go Green program, one of which is limiting/reducing the useof paper (paperless), it is necessary to have an application that can fulfill the activities such as UTS andUAS which adopt the UNBK application system. The application was developed using a SystemDevelopment Life Cycle (SDLC) approach using the waterfall model and using the PHP and HTMLprogramming languages, and the database used MySQL. The tools and editors used are Sublime andAndroid Studio. The web-based exam application can be accessed by admins and teachers via PC/laptop,while the mobile-based exam application can only be accessed by all students via smartphones with theAndroid operating system..